Delayed Breast Reconstruction on Patients With Upper Extremity Lymphedema: A Systematic Review of the Literature and Pooled Analysis. Issue 6 (December 2018) - Siotos, Charalampos; Hassanein, Aladdin H.; Bello, Ricardo J.; Sebai, Mohamad E.; Seal, Stella M.; Manahan, Michele A.; Cooney, Damon S.; Cooney, Carisa M.; Rosson, Gedge D.
Abstract : Background: Breast cancer–related lymphedema (BCRL) is a debilitating condition with morbidity, hindered quality of life, and increased health-related costs. Experimental studies support the use of musculocutaneous flaps for managing animal models with lymphedema. Although vascularized lymph node transfer (VLNT) and lymphovenous anastomosis are used to surgically treat patients with lymphedema, it is not known whether musculocutaneous or adipocutaneous flaps (eg, delayed autologous breast reconstruction) are effective for treating refractory upper extremity BCRL. We conducted a systematic review and pooled analysis to assess the impact of delayed breast reconstruction on developed BCRL. Methods: Following PRISMA guidelines, we systematically searched PubMed, Scopus, EMBASE, and Google Scholar databases for relevant studies published through November 11, 2016. We screened 934 unique articles. Of these, we conducted full-text and reference screening on 37 articles. We then performed a pooled and sensitivity analysis using random effects. Results: Eight studies met our inclusion criteria. One study was a case report; 7 studies were case series with sample sizes ranging from 3 to 38 patients. According to our pooled analysis 58% of patients reported improvement after breast reconstruction with or without VLNT. Sensitivity analysis revealed that 84% (95% confidence interval, 0.74–0.95) of patients who underwent breast reconstruction and VLNT reported improvement, whereas only 22% (95% confidence interval, 0.12–0.32) of those who had breast reconstruction alone reported improvement. Conclusions: Our review summarizes the current evidence regarding the effect of delayed breast reconstruction on established lymphedema. The VLNT component of the autologous breast reconstruction procedures may be the largest contributing factor leading to lymphedema improvement.